2011
DOI: 10.1161/circulationaha.110.015453
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Everolimus-Eluting Stent Versus Sirolimus-Eluting Stent Implantation for De Novo Coronary Artery Disease in Patients With Diabetes Mellitus (ESSENCE-DIABETES)

Abstract: on behalf of the ESSENCE-DIABETES Study InvestigatorsBackground-Drug-eluting stents significantly improved angiographic and clinical outcomes compared with bare metal stents in diabetic patients. However, a comparison of everolimus-eluting stents and sirolimus-eluting stents in diabetic patients has not been evaluated. Therefore we compared effectiveness of everolimus-eluting stents and sirolimus-eluting stents in patients with diabetes mellitus. Methods and Results-This prospective, multicenter, randomized st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 31 publications
6
68
2
2
Order By: Relevance
“…SES was available in diameters of 2.50, 2.75, 3.00, and 3.50 mm, and in lengths of 8,13,18,23, and 28 mm for stents with a diameter of 2.50 mm, 18 mm, and 23 mm for stents with a diameter of 2.75 mm, and 8, 13, 18, 28, and 33 mm for stents with diameters of 3.00 mm, and 3.50 mm. Use of stents other than the assigned study stent was not allowed unless the delivery of the assigned stent was unsuccessful, in which case crossover to any commercially available coronary stents including the comparator study stent was permitted.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…SES was available in diameters of 2.50, 2.75, 3.00, and 3.50 mm, and in lengths of 8,13,18,23, and 28 mm for stents with a diameter of 2.50 mm, 18 mm, and 23 mm for stents with a diameter of 2.75 mm, and 8, 13, 18, 28, and 33 mm for stents with diameters of 3.00 mm, and 3.50 mm. Use of stents other than the assigned study stent was not allowed unless the delivery of the assigned stent was unsuccessful, in which case crossover to any commercially available coronary stents including the comparator study stent was permitted.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Third, although the noninferiority margin of 0.195 mm in the angiographic substudy was defined according to that used in the SPIRIT III trial, it seems disproportionate to the actual sizes of in-segment late loss in the current study. If we choose the noninferiority margin of 0.15 mm used in the Randomized Comparison of EverolimusEluting Stent Versus Sirolimus-Eluting Stent Implantation for De Novo Coronary Artery Disease in Patients with Diabetes Mellitus (ESSENCE-DIABETES) trial, 13 noninferiority of EES could still be declared in the current study (P noninferiority ϭ0.002). If we choose the noninferiority margin of 0.1 mm used in the Efficacy of Xience/Promus Versus Cypher to Reduce Late Loss After Stenting (EXCELLENT) and Percutaneous Treatment of LONG Native Coronary Lesions With Drug-Eluting Stent-III (LONG-DES-III) trials, 9,14 noninferiority of EES was not met in the current study (P noninferiority ϭ0.1).…”
Section: Study Limitationsmentioning
confidence: 99%
“…25,26 Similarly, studies of EES versus SES in diabetic patients found that EES are associated with lower rates of restenosis than SES. 27 In comparison, a pooled analysis of randomised studies found no difference in efficacy or safety of EES versus PES among diabetic patients, suggesting that EES may not have significant benefit compared to PES. 28 Based on conflicting data with outcomes of different DES types among patients with diabetes, the recently reported Taxus …”
Section: Stent Type and Outcomes Among Patients With Diabetesmentioning
confidence: 98%
“…Everolimus-eluting stents have shown so far very favorable results in the SPIRIT clinical trial program as well as in other independent studies [18][19][20], with outstanding reductions in neointimal hyperplasia and ensuing risks of binary restenosis, target lesion revascularization, target vessel revascularization, and major adverse cardiac events. Such inhibitory effects on smooth muscle cells appear associated with a very favorable impact on endothelial function and strut coverage, at least in light of the risk of stent thrombosis associated with these devices.…”
Section: Second-generation Drug-eluting Stentsmentioning
confidence: 99%